EXTH-83. DEVELOPMENTALLY REGULATED ANTIGENS FOR IMMUNOLOGIC TARGETING OF EMBRYONAL PEDIATRIC BRAIN CANCERS. (14th November 2022) - Sebastian, Mathew; Pham, Christina; Wummer, Brandon; Woodworth, Delaney; Reid, Alexandra; Abraham, Rebecca; Gil, Jorge; Drake, Jeffrey; Mitchell, Duane; Flores, Catherine
Abstract: BACKGROUND: Mutated neoantigens have shown promise as targets for cancer immunotherapy but embryonal pediatric brain tumors with notoriously low mutational burden have more limited opportunities for neoantigen directed therapies. Evidence suggests that embryonal brain tumors such as medulloblastoma (MB) and brain stem gliomas (BSG) arise from the aberrant reactivation of fetal developmental programming. We explored the hypothesis that neonatal mouse cerebellum and brainstem express developmentally regulated proteins that could serve as potent tumor rejection antigens for a preclinical model of Group 3 MB (NSC) and H3.3K27M positive BSG (K2), respectively. We thus generated tumor-reactive T cells by using P5 cerebellum and P4 brain stem RNA as sources of antigens. P5-cerebellum-specific T cells (cDevAg-T cells) and P4-brain stem-specific T cells (bsDevAg-T cells) demonstrated effector function against respective MB and BSG tumor cells with exquisite specificity. METHODS: RNA was isolated from P5 cerebellum and P4 brain stem and pulsed into bone marrow-derived dendritic cells. These were then used to in vitro activate splenocytes from previously immunized mice, generating either cDevAg-T cells or bsDevAg-T cells. In vitro functionality assays against tumor targets were conducted to determine reactivity and specificity. DevAg-T cells were used in adoptive cellular therapy in orthotopic models to determine therapeutic efficacy of DevAg-specific T cells in vivo. Results and CONCLUSIONS: DevAg-T cells produce high levels of Th1-type cytokines that recognize distinct subtypes of MB and BSG, show no cross-reactivity with normal brain. Adoptive cellular therapy employing DevAg-specific T cells demonstrate a significant survival benefit in orthotopic models of established Group 3 NSC MB and H3.3K27M mutation positive BSG. Our studies demonstrate that RNA encoding non-mutated and organ-specific developmental antigens can serve as novel tumor rejection antigens for pediatric brain cancers.